2014
DOI: 10.1016/j.toxrep.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of bromobenzene hepatotoxicity by Withania somnifera pretreatment: Role of mitochondrial oxidative stress

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…Furthermore, ASHW was observed to reduce liver toxicity and damages in the CAIA mice through a reduction in the stimulated levels of Alanine Aminotransferase (ALT) and Aspartate Aminotransferase (AST), in blood serum. This in line with several other studies that have reported the role of Withania somnifera extracts in improving liver functions and in ameliorating chemicals induced hepatotoxicity 3436 .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, ASHW was observed to reduce liver toxicity and damages in the CAIA mice through a reduction in the stimulated levels of Alanine Aminotransferase (ALT) and Aspartate Aminotransferase (AST), in blood serum. This in line with several other studies that have reported the role of Withania somnifera extracts in improving liver functions and in ameliorating chemicals induced hepatotoxicity 3436 .…”
Section: Discussionsupporting
confidence: 92%
“…NF-κB was normally sequestered in an inactiveform in the cytoplasm bound to IκB proteins, an interaction that regulated its activity [20] , [21] , [22] . Multiplestimuli can activate NF-κB signaling by degradation of IκB and release of the NF-κB p65–p50 dimer, which translocated to the nucleus, binds to κB binding sites on DNA, and regulated transcriptional activation of the target genes [39] , [40] , [41] , [42] , [43] . NF-κB was an important nuclear transcription factor in eukaryotic cells, which existed in almost all the cells [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, roots are consumed as a dietary supplement. Previous pharmacological studies on W. somnifera have revealed that extracts of W. somnifera exhibit a protective role against bromobenzene-induced oxidative damage in the rat liver [7], as well as increase the exercise performance [8]. Similarly, a recent study on W. somnifera extracts reported its therapeutic role in stroke repair through its anti-apoptotic and anti-oxidant properties [9].…”
Section: Introductionmentioning
confidence: 95%